Role of the Renin-Angiotensin System and Aldosterone on Cardiometabolic Syndrome - P. Stiefel; A. J. Vallejo-Vaz; S. García Morillo; J. Villar (International Journal of Hypertension)
Aldosterone facilitates cardiovascular damage by increasing blood pressure and through different mechanisms that are independent of its effects on blood pressure. In this respect, recent evidence involves aldosterone in the pathogenesis of metabolic syndrome. Although this relationship is complex, there is some evidence suggesting that different factors may play an important role, such as insulin resistance, renin-angiotensin-aldosterone system, oxidative stress, sodium retention, increased sympathetic activity, levels of free fatty acids, or inflammatory cytokines and adipokines. In addition to the classical pathway by which aldosterone acts through the mineralocorticoid receptors leading to sodium retention, aldosterone also has other mechanisms that influence cardiovascular tissue remodelling. Finally, overweight and obesity promote the adrenal secretion of aldosterone, increasing the predisposition to type 2 diabetes mellitus. Further studies are needed to better establish therapeutic strategies that act on the blockade of mineralocorticoid receptor in the treatment and prevention of cardiovascular diseases related to the excess of aldosterone and the metabolic syndrome.